An annotated checklist of the Recent non-marine ostracods (Ostracoda: Crustacea) from Italy - Pieri, Valentina; Martens, Koen; Meisch, Claude; Rossetti, Giampaolo (Zootaxa, 2015)
We present an updated checklist of non-marine ostracods from Italy. Data were obtained from the published literature up to April 2013 and new collections carried out in 18 out of 20 Italian regions. Altogether, 1665 ostracod samples were collected from 1241 new sites visited between 1981 and 2013. Sites were selected to encompass the most widespread types of freshwater aquatic habitats (i.e., pools, ponds, peat bogs, springs and streams, etc.). This field study led to the identification of 89 ostracod species. Five additional taxa remained at the generic level because only few (juvenile) individuals were available or the material was damaged. Of particular interest is the occurrence of four species new to Italy: Candonocypris novaezelandiae, Eucypris elongata, Ilyocypris getica and I. hartmanni. In addition, three putative new species (Pseudolimnocythere sp., Candona sp.1 and Eucypris sp.1) are left in open nomenclature. After synonymising several species and removing invalid taxa reported in the literature, the updated checklist now includes 152 species and 5 taxa identified at supraspecific level, belonging to 57 genera and 12 families (Candonidae, Cyprididae, Cytherideidae, Darwinulidae, Ilyocyprididae, Notodromadidae, Limnocytheridae, Leptocytheridae, Loxochonchidae, Hemicytheridae, Xestoleberididae and Entocytheridae). For each species, its distribution in Italy and its bibliographic records (including synonyms) for Italy are provided.